The Comparison Exstracts Of Sambiloto Leaves and roots (Andrographis paniculata) On the Mortality Of Head Lice (Pediculus humanus capitis) - Ayu Ferra Dwi Lestari; Ayu Tri Agustin; Ahdiah Imroatul Muflihah (Journal of Medical Laboratory in Infectious and Degenerative Diseases, 2026)
Abstract Background: The head lice (Pediculus humanus capitis is an ectoparasite that causes pediculosis capitis, a condition that remains prevalent in densely populated areas such as Islamic boarding schools. Sambiloto (Andrographis paniculata) is known as a traditional medicinal plant containing bioactive compounds—specifically secondary metabolites—that exhibit natural insecticidal activity. Methods: This study used an experimental study design with a Post Only Control group design. The study was conducted in May-June 2025 at the integrated laboratory of Universitas dr. Soebandi, Jember. This study used lice samples obtained from the X Islamic boarding school in Tempurejo village, Jember Regency, as many as 240 lice samples divided into 6 treatment groups. Purposive sampling was used to select the study participants, from whom the head lice specimens were collected. Data were analyzed using both descriptive and statistical methods. Results: The result of this study indicate that the extract of sambiloto leaves and roots on the death of head lice there is a significant difference (p<0.05). The result of the Dunn test analysis identified six significant comparisons, namely negative control – positive control (0.000), negative control – root 40% (0.029), negative control – root 50% (0.031), leaf 40% - positive control (0.002), and leaf 50% - positive control (0.006). The results of this tudyy obtained the death of head lice in the 50% leaf treatment reached 5, while the highest death of head lice was found in the 50% root. Conclusions: The most effective extract sambiloto leaves and roots (Andrographis paniculata) killing head lice (Pediculus humanus capitis) is 50% of the roots within 45 minutes.